DEVELOPMENT AND VALIDATION OF A SELECTIVE LIQUID CHROMATOGRAPH WITH TANDEM MASS SPECTROMETRY METHOD FOR SIMULTANEOUS ESTIMATION OF SEMAGLUTIDE AND ERTUGLIFLOZIN IN HUMAN PLASMA - JAGAPATHI RAJU VATSAVAYI; NALANDA BABY REVU (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: The objective of the study was to develop a method capable of simultaneously estimation of semaglutide and ertugliflozin to support pharmacokinetic and bioequivalence studies. Methods: An organized protein precipitation extraction technique was used for estimation of semaglutide and ertugliflozin. The two compounds were separated on an Agilent Zorbax C18 (50 mm × 2.1 mm, 5 μ Particle size) column, using an electro spray ionization with a positive ionization mode on a liquid chromatograph with tandem mass spectrometry instrument. Verapamil was the chosen internal standard for this estimation. The quantification was carried out using a multiple reaction monitoring method and a gradient program utilizing acetonitrile and 0.1% formic acid in water as mobile phases to achieve a separation in 2.2 min. Results: The method established was performing linearly over a working range of 1.00–1000 ng/mL for semaglutide (r2>0.98) and Ertugliflozin (r2>0.98) in human plasma. The validation parameters consisted of specificity, selectivity, precision, accuracy, recovery, matrix effects, and stability, which were within acceptable limits. The stability was established in compliance with the International Council for Harmonization guideline M10 on Bioanalytical method validation. Conclusion: This method was selective and with suitable sensitivity at the 1.00 ng/mL as the lower limit of quantification employed for semaglutide and Ertugliflozin. It can be utilized for quantification in human plasma and will facilitate the further application to exploratory formulation studies for the combination of these two drugs in pharmaceutical dosage forms.